Training on Floating Cage Product Diversification Strategy in Margaluyu Village, Pangalengan, Bandung - Prawesti, Gita; Isniah, Sarah; Supriatna, Ade; Syamsyiah, Nur; Yahya, Yahya; Hasanah, Nur (Journal of Universal Community Empowerment Provision, 2024)
Margaluyu Tourist Village is located in Pangalengan, Bandung Regency, West Java. The community groups in Margaluyu Village consist of vegetable farmers, dairy cattle breeders, honeybee farmers, ecotourism groups, MSME practitioners, floating cage fishermen, integrated health post cadres, and teachers. The processing of floating cages' products lacks variation, resulting in limited market share availability. The community service method carried out is by providing material presentations about strategies for diversifying floating cage products so that floating cage fishermen can increase their market share through service learning. This method consists of three activity stages, namely the preparation stage, implementation stage and evaluation stage. At the end of the presentation, 75% of participants were able to determine the use of diversification and were able to determine the processed fish products to be sold. So the final result was 84.4% of participants were able to understand the presentation of the material given.